Effects of feeding different levels on digestibility body weight body condition score and stool quality in dogs - Kahraman, Oğuzhan; İnal, Fatma; İnanç, Zekeriya Safa (Afyon Kocatepe Üniversitesi)
n this study, effects of different levels of feeding on digestibility, body weight(BW), body condition score(BCS) and some stool parameters were investigated. Fifteen adult Golden Retriever dogs were divided into 3 groups. ME content of food and ME requirements of the dogs were determined by the modified Atwater factors and the FEDIAF equation(95*BW0.75). The first group was fed 50% less than daily metabolic energy requirement(MER)(1), second group was fed 100%(2) and the third group was fed 50% more than the MER(3). Trial lasted 15 days. Stools were scored and stool samples were taken in last 4 days of the study. Dry matter(DMD) and organic matter digestibilities(OMD) were determined by acid-insoluble ash indicator method. BW and BCS values were determined on the 7th and 15th days. Changes in BW and BCS between days and groups were insignificant(P>0.05). DMD and OMD values were the highest in groups 1 and 2(P<0.05). Group 1 had the highest stool score(P<0.05). There was no significant difference in stool DM levels between all groups(P>0.05). In conclusion, modified Atwater factors and formula 95*BW0.75 were sufficient to preserve BW and BCS for this 15-day study. More studies are needed to compare the different formulas used to calculate the energy needs of dogs and the energy content in their diets. BW and BCS changes should be demonstrated with long-term trials. Effects of daily amount of food determined by the formulas on digestibility and health of dogs should also be investigated.

Bu çalışmada farklı düzeylerde beslemenin sindirilebilirlik, canlı ağırlık(CA), vücut kondüsyon skoru(VKS) ve bazı dışkı parametreleri üzerine etkileri araştırıldı. Onbeş yetişkin Golden Retriever köpek 3 gruba ayrıldı. Mamanın ME içeriği ve köpeklerin ME gereksinimleri, modifiye Atwater faktörleri ve FEDIAF denklemi(95*CA0.75) ile belirlendi. Birinci grup günlük metabolik enerji ihtiyacından(MEİ) %50 daha az(1), ikinci grup ihtiyacın %100’ü(2) ve üçüncü grup MEİ(3)'dan %50 daha fazla olacak düzeyde beslendi. Deneme 15 gün sürdü. Çalışmanın son 4 gününde dışkı skorlaması yapıldı ve dışkı numuneleri alındı. Kuru madde(KMS) ve organik madde sindirilebilirliği(OMS) asitte çözünmeyen kül indikatör yöntemi ile belirlendi. CA ve VKS değerlerindeki değişimler 7. ve 15. günlerde belirlendi. Günler ve gruplar arasındaki CA ve VKS değişiklikleri önemsizdi(P>0.05). KMS ve OMS değerleri grup 1 ve 2'de en yüksekti(P<0.05). Grup 1 en yüksek dışkı skoruna sahipti(P<0.05). Her üç grubun dışkı KM düzeyleri arasında anlamlı bir fark yoktu(P>0.05). Sonuç olarak, 15 gün süren bu çalışma için modifiye Atwater faktörleri ve 95*CA0.75 formülü CA ve VKS’yi korumada yeterliydi. Köpeklerin enerji ihtiyaçlarını ve diyetlerindeki enerji içeriğini hesaplamada kullanılan farklı formüllerin karşılaştırılmalı olarak değerlendirildiği daha fazla çalışmaya ihtiyaç vardır. CA ve VKS’ye etkileri uzun süren denemelerle ortaya konulmalıdır. Formüllerle belirlenen günlük mama miktarının köpeklerde sindirilebilirlik ve sağlığa etkileri de araştırılmalıdır.
Farklı düzeylerde beslemenin köpeklerde sindirilebilirlik canlı ağırlık vücut kondüsyon skoru ve dışkı kalitesi üzerine etkileri
Keywords: Atwater Factors; Body Condition Score; Digestibility; Dog; Metabolizable Energy; Atwater Faktörleri; Köpek; Sindirilebilirlik; Metabolik Enerji; Vücut Kondisyon Skoru